TECHNOLOGY INTEGRATION IN ENGLISH LANGUAGE LEARNING BASED ON THE TPACK-SAMR FRAMEWORK AT THREE INDONESIAN UNIVERSITIES - Ahmada, Adib; Rizkiyah, Faiqotur (IJEE (Indonesian Journal of English Education), 2024)
Technology plays a crucial role in various aspects of human life, especially in education, making the integration of technology in English language learning at the university level essential. This study aims to: 1) analyze how lecturers integrate technology; 2) Evaluate the proficiency of English language lecturers in incorporating technology using the TPACK-SAMR framework; 3) investigate the implications of technology integration based on TPACK-SAMR in English Language Teaching (ELT). This research employed mixed method approach which involved six lecturers from three Indonesian universities. Interviews and questionnaires were administered to obtain the data. Furthermore, the data was analyzed both qualitative involving data reduction, data display, and conclusion drawing or verification and statistical analysis using SPSS 25..  . The results show that the six lecturers at the universities have integrated technology into their teaching, including preparation, implementation, and assessment. In terms of integration level based on TPACK-SAMR, the lecturers are well-qualified in the aspects of pedagogy, content, and technology. For SAMR levels, the amount of technology integration in learning has reached the point where substitution and augmentation are widespread practices among lecturers. However, the application of technology at the modification and redefinition levels remains limited. Moreover, technology has the results revealed six noteworthy aspects of implication technology in English classroom, namely enrichment of learning material, enhanced learning, accessibility, a broader range of assessment, provide direct feedback and enhanced productivity and efficacy. therefore, lecturers' TPACK-SAMR competency in the practice of using technology is very important as a basis for the application of technology in higher education in the future.